Gold-Catalyzed, SN1-Type Reaction of Alcohols to Afford Ethers and Cbz-Protected Amines - Vinson, Andrew R. S.; Davis, Victoria K.; Arunasalam, Arunamarie; Jesse, Kate A.; Hamilton, Rachael E.; Shattuck, Morgan A.; Hu, Allison C.; Iafe, Robert G.; Wenzel, Anna G. (Synlett, 2015)
The use of a gold-catalyzed, microwave protocol to activate alcohols through an intermolecular, SN1-type reaction to directly form unsymmetrical ethers and N-benzyloxy carbamate- (Cbz) protected amines is reported. Results have shown this reaction to be highly reproducible and tolerant of moisture, and moderate to high product yields (53–99%) were obtained. Significantly, the intermolecular catalytic amination of alcohols to directly afford Cbz-protected amines is heretofore unprecedented using gold catalysis.
Keywords: gold; catalysis; ethers; amination; substitution